DIFFERENTIAL APPROACH TO ADENOMYOSIS TREATMENT - I. S. Sidorova; A. L. Unanyan (IRBIS LLC, 2016)
This article presents results of authors' own investigations using a new approach to treatment of adenomyosis (uterine endometriotic lesions which are most often found within the structure of genital endometriosis) and differential characteristics of different (by their activity) forms of disease. The investigation included 492 female patients. Depending on the intensity of main clinical manifestations characteristic for adenomyosis, the examined females were divided into 2 groups: the 1st group comprised 344 patients with clinically active adenomyosis, and the second group included 148 patients with clinically inactive adenomyosis. 321 (65.2%) out of 492 (100%) adenomyosis patients were subjected to separate therapeutic and diagnostic endocervical and uterine cavity curettage followed by hysterectomy. 171 (34.8%) of females have received a course of conservative treatment (in 114 patients of the total - after separate diagnostic curettage). 113 adenomyosis patients (64 from group I and 49 from group II - without hysterectomy) have received a 6-month course of treatment by GnRh-A (gonadotropin-releasing hormone agonists) with pronounced positive effect. After completion of the GnRh-A course, a complex treatment was used with monophasic combination oral contraceptives (OC) in the extended regimen. This approach is highly efficacious and to a large extent enables to put into effect the organ-saving tactics of adenomyosis treatment which is particularly important in the reproductive age.